THE EFFECT OF OKETANI MASSAGE ON BREASTFEEDING MOTHERS WITH BREAST MILK DAMS: A NARRATIVE REVIEW - Enny Nahumuri; Mardiana Ahmad; Aryadi Arsyad; Nur Aliya Arsyad (Nurse and Health: Jurnal Keperawatan, 2022)
At the beginning of labor, the pain experienced after childbirth often makes the mother lazy to breastfeed her baby. Factors that affect failure in the process such as swollen breasts, mastitis, nipples, breast milk have not come out, and improper breastfeeding techniques. In the postpartum period, if the baby has not suckled and the breast glands are not emptied ideally, there will be a dam of milk, heat and hard, pain when groaned, nipples can flatten so that it can take the baby to suckle. This study aimed to find out the effect of Oketani massage on nursing mothers with breast milk dam. This research design is a narrative review to find and review articles from databases and theories that are descriptive. Search articles using databased ScienceDirect by entering the keyword "Oketani message, breastfeeding, milk production" obtained nine reports based on the criteria that have been set. Literature review method by filtering on the Mendeley website based on inclusion criteria, then collected and made a summary of the journal including the name of the researcher, year of publication of the journal, research title, method, and overview of results or findings. An article search by entering keywords found 39 relevant articles; after filtering, nine articles were reviewed and met the inclusion criteria; it is reported that the Oketani message will make the breasts softer, make the areola and nipples more elastic, making it easier for the baby to suckle. Breast milk flow becomes smoother because of pressure on the alveoli. The Oketani massage technique has eight steps, seven of which are in the retro mammary and one on the right and left sides of the breast (the areola area containing the myoepithelium). An Oketani massage performed for 15-20 minutes has an effect on nursing mothers with breast milk dams.